Pictograms as an Augmentative and Alternative Communication (AAC) Model to Promote Oral Communication in an Autistic Child in Spanish - Saravia Arguelles, Leidy Angelica (Corporación Universitaria Minuto de Dios, 2022)
This work is a proposal to design a lesson plan based on the method of augmentative and alternative communication (AAC). The purpose is to help a child with autism spectrum disorder (ASD). The lesson plan has features such as executive functions and pictograms. The lesson plan goal is to help regular students and students with special needs increase their vocabulary or recover it.
Designing lessons plans during six interventions using an alternative and augmentative model in the oral communication to a child with ASD
Keywords: Special Needs Education; Autism Spectrum Disorder; Pictograms; Executive Functions